Factors Related with Musculoskeletal Disorders on Garbage Carrier Workers - Annisa, Yunia Zahra; Firdani, Fea; yani, Fitri (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
Garbage collectors carry out manual work that requires physical strength when lifting and moving rubbish, which puts them at risk of experiencing Musculoskeletal Disorders complaints. Based on preliminary studies, 70% of waste collection officers in Padang City 2023 will experience serious MSD complaints. This research aims to determine the factors related to MSD complaints among waste collection officers in Padang City. This research used a cross-sectional design conducted from January to July 2023 with a population of 131 people and a sample of 62 people selected using Accidental Sampling. Data analysis techniques use univariate analysis, bivariate analysis (chi-square), and multivariate (multiple logistic regression). 61.3% of workers experienced complaints of severe MSDs, 61.3% had age at risk, 32.2% had abnormal BMI, 54.8% had long working periods, 79% had unergonomic working postures, and 53.2% had moderate physical workload. Variables related to MSDs were age (p=0.000), years of work (p=0.000), work posture (p=0.004), and physical workload (p=0.026). Variables unrelated to MSD complaints were (p=0.893) and repetitive movements (p=0.448). The most dominant variable related to MSD complaints was length of service (p=0.008). There is a relationship between age, years of work, work posture, and physical workload with MSD complaints. The working period is the most dominant variable related to MSD complaints. We hope that workers carry out routine muscle stretching before work and provide education on ergonomic working methods for garbage carrier workers.